Comfort Discussing HIV Pre-exposure Prophylaxis With Patients Among Physicians in an Urban Emergency Department. (1st February 2019) - Tortelli, Brett A.; Char, Douglas M.; Crane, John S.; Powderly, William G.; Salter, Amber; Chan, Philip A.; Patel, Rupa R.
Abstract : Supplemental Digital Content is Available in the Text.